Quadriceps Muscle Fatigue Reduces Extension and Flexion Power During Maximal Cycling - O'Bryan, Steven J.; Taylor, Janet L.; D'Amico, Jessica M.; Rouffet, David M. (Frontiers in Sports and Active Living, 2022)
Purpose: To investigate how quadriceps muscle fatigue affects power production over the extension and flexion phases and muscle activation during maximal cycling. Methods: Ten participants performed 10-s maximal cycling efforts without fatigue and after 120 bilateral maximal concentric contractions of the quadriceps muscles. Extension power, flexion power and electromyographic (EMG) activity were compared between maximal cycling trials. We also investigated the associations between changes in quadriceps force during isometric maximal voluntary contractions (IMVC) and power output (flexion and extension) during maximal cycling, in addition to inter-individual variability in muscle activation and pedal force profiles. Results: Quadriceps IMVC (−52 ± 21%, P = 0.002), voluntary activation (−24 ± 14%, P < 0.001) and resting twitch amplitude (−45 ± 19%, P = 0.002) were reduced following the fatiguing task, whereas vastus lateralis (P = 0.58) and vastus medialis (P = 0.15) M-wave amplitudes were unchanged. The reductions in extension power (−15 ± 8%, P < 0.001) and flexion power (−24 ± 18%, P < 0.001) recorded during maximal cycling with fatigue of the quadriceps were dissociated from the decreases in quadriceps IMVC. Peak EMG decreased across all muscles while inter-individual variability in pedal force and EMG profiles increased during maximal cycling with quadriceps fatigue. Conclusion: Quadriceps fatigue induced by voluntary contractions led to reduced activation of all lower limb muscles, increased inter-individual variability and decreased power production during maximal cycling. Interestingly, power production was further reduced over the flexion phase (24%) than the extension phase (15%), likely due to larger levels of peripheral fatigue developed in RF muscle and/or a higher contribution of the quadriceps muscle to flexion power production compared to extension power during maximal cycling.